2023
DOI: 10.1002/jobm.202300454
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the effects of zinc oxide and titanium dioxide nanoparticles on the formation of biofilm and persister cells in Klebsiella pneumoniae

Aisouda Pourmehdiabadi,
Mojgan Sarabi Nobakht,
Behdad Hajjam Balajorshari
et al.

Abstract: The biofilm formation in klebsiella pneumoniae isolates poses a significant problem as it can result in treatment failure and the development of chronic infections. These biofilms act as protective barriers, rendering the bacteria resistant to antibiotics. Additionally, persister cells, which make up a small fraction of the bacterial population, have the ability to enter a dormant state after treatment with high doses of antibiotics. These persister cells play a crucial role in the high level of biofilm‐mediat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
(33 reference statements)
0
3
0
Order By: Relevance
“…They investigated the expression of genes in Klebsiella pneumoniae, which has a role in bacterial persistence, under nanoparticle exposure and compared it with the expression of untreated bacteria as a control. They showed that another antibiofilm mechanism of NPs can be the change in gene expression in biofilm production [26].…”
Section: Studies On Antimicrobial and Antibiofilm Effects Of Tio 2 Na...mentioning
confidence: 99%
See 2 more Smart Citations
“…They investigated the expression of genes in Klebsiella pneumoniae, which has a role in bacterial persistence, under nanoparticle exposure and compared it with the expression of untreated bacteria as a control. They showed that another antibiofilm mechanism of NPs can be the change in gene expression in biofilm production [26].…”
Section: Studies On Antimicrobial and Antibiofilm Effects Of Tio 2 Na...mentioning
confidence: 99%
“…Intensive care units are mainly affected due to the multitude of maneuvers and invasive devices, but also due to the severity of the diagnoses of hospitalized patients and the large number of days of hospitalization [4,5,25]. Patients with bacteremia or respiratory infections due to carbapenemase-producing Klebsiella pneumoniae present a high death rate (30-70%) [4,5,25,26]. In our intensive care unit, we also face this major problem.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation